Condom use at last sexual relationship among adolescents of Santiago Island, Cape Verde, - West Africa - Tavares, Carlos Mendes; Schor, Neia; Valenti, Vitor Engrácia [UNESP]; Sugishita Kanikadan, Paula Yuri; de Abreu, Luiz Carlos (Biomed Central Ltd., 2012)
Objective: To estimate factors associated with condom use at last sexual intercourse among adolescents.Methods: Cross-sectional study of a representative sample of 368 sexually active adolescents aged 13-17 years from eight public high schools on Santiago Island, Cape Verde, 2007. The level of significance was 5.0% obtained from logistic regression, considering the association between condom use and socio-demographic, sexual and reproductive variables.Results: The prevalence of condom use at last sexual intercourse was 94.9%. Factors associated with condom use at last sexual relationship were: non-Catholic religion (OR=0.68, 95%CI: 0.52; 0.88) and affective-sexual partnership before the interview (OR=5.15, 95%CI: 1.79; 14.80).Conclusions: There was a high prevalence of condom use at last sexual intercourse of adolescents.
Keywords: Adolescent health; Condom; Condom use; Sexual and reproductive health; Cape Verde; West Africa